1996
DOI: 10.1172/jci119101
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor modulation of basal and beta-adrenergic stimulated function of the failing human left ventricle.

Abstract: The objective of this study was to evaluate the effect of muscarinic receptor modulation on basal and ␤ -adrenergic stimulated left ventricular function in patients with heart failure. 21 heart failure patients and 14 subjects with normal ventricular function were studied. In Protocol 1 intracoronary acetylcholine resulted in a 60 Ϯ 8% inhibition of the left ventricular ϩ dP/dt response to intracoronary dobutamine in the normal group, and a similar 70 Ϯ 13% inhibition in the heart failure group. Acetylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The administration of dobutamine by the intravenous or intracoronary route is a well-established method of assessing ␤-adrenergic responsiveness in humans. 11,20,22 In this study, the vitamin C-mediated augmentation of the dobutamine response was similar in magnitude to that observed with parasympathetic blockade in humans with normal ventricular function 11 as well as nitric oxide synthase blockade in patients with CHF. 20 In the experimental group, it is unlikely that the inotropic response to the second dobutamine infusion was potentiated by the previous dobutamine infusion, because no significant difference in the dP/dt response was observed between successive dobutamine infusions in the control group.…”
Section: Discussionsupporting
confidence: 79%
“…The administration of dobutamine by the intravenous or intracoronary route is a well-established method of assessing ␤-adrenergic responsiveness in humans. 11,20,22 In this study, the vitamin C-mediated augmentation of the dobutamine response was similar in magnitude to that observed with parasympathetic blockade in humans with normal ventricular function 11 as well as nitric oxide synthase blockade in patients with CHF. 20 In the experimental group, it is unlikely that the inotropic response to the second dobutamine infusion was potentiated by the previous dobutamine infusion, because no significant difference in the dP/dt response was observed between successive dobutamine infusions in the control group.…”
Section: Discussionsupporting
confidence: 79%
“…The absence of an atropine effect on cardiac sympathetic activity in subjects with CHF is consistent with previous observations that have documented that heart failure represents a state of parasympathetic withdrawal. 5,6,18 This is known to occur at the level of the sinus node, 27 and our laboratory has recently confirmed decreased parasympathetic input to the failing human left ventricle. 18 These observations, taken together, suggest that abnormalities in cardiac parasympathetic tone may be one factor that contributes to the increase in cardiac sympathetic activity seen in the setting of CHF.…”
Section: Azevedo and Parker Muscarinic Control Of Cardiac Sympatheticmentioning
confidence: 69%
“…This does not appear to be the case, because in a previous report we have demonstrated that the same estimated intracoronary concentration of atropine completely inhibited the hemodynamic effects of acetylcholine. 18 Because this concentration of acetylcholine also caused potent inhibitory effect on cardiac sympathetic activity in the CHF group, we believe that the dose of atropine used was adequate to provide blockade of myocardial muscarinic receptors.…”
Section: Azevedo and Parker Muscarinic Control Of Cardiac Sympatheticmentioning
confidence: 94%
See 1 more Smart Citation
“…Congestive heart failure (HF), a disease with high mortality and increasing prevalence, 1 is characterized by autonomic imbalance, including decreased parasympathetic tone, 2,3 hyperactive sympathetic tone 4,5 and impaired baroreflex control of sympathetic activity. 6,7 Pharmacotherapy attempting to restore the autonomic imbalance with drugs such as beta-blockers, angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers, and aldosterone receptor antagonists have been shown to improve survival among HF patients and are recommended for HF patients with reduced ejection fraction.…”
Section: Introductionmentioning
confidence: 99%